2006
DOI: 10.1002/humu.20310
|View full text |Cite|
|
Sign up to set email alerts
|

Jagged1 (JAG1) mutations in Alagille syndrome: increasing the mutation detection rate

Abstract: Alagille syndrome (AGS) is caused by heterozygous mutations in JAG1, and mutations have been previously reported in about 70% of patients who meet clinical diagnostic criteria. We studied a cohort of 247 clinically well-defined patients, and using an aggressive and sequential screening approach we identified JAG1 mutations in 94% of individuals. Mutations were found in 232 out of 247 patients studied and 83 of the mutations were novel. This increase in the mutation rate was accomplished by combining rigorous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(115 citation statements)
references
References 27 publications
4
108
2
1
Order By: Relevance
“…120 In addition, mutations in the Notch2 locus have been identified in patients with Jagged1-independent AGS. 121 AGS is an autosomal dominant disorder most commonly associated with neonatal jaundice and impaired development of intrahepatic bile ducts with additional abnormalities of the eye, heart, kidney, and skeleton, with variable penetrance.…”
Section: Alagille Syndromementioning
confidence: 99%
“…120 In addition, mutations in the Notch2 locus have been identified in patients with Jagged1-independent AGS. 121 AGS is an autosomal dominant disorder most commonly associated with neonatal jaundice and impaired development of intrahepatic bile ducts with additional abnormalities of the eye, heart, kidney, and skeleton, with variable penetrance.…”
Section: Alagille Syndromementioning
confidence: 99%
“…Most cases are caused by point mutations but a few (3%-7%) have 20p micro-deletion of variable size. [4] Using an aggressive and sequential screening approach combined with mutation detection techniques and rigorous clinical phenotyping, Warthen et al [11] identifi ed JAG1 mutations …”
Section: Discussionmentioning
confidence: 99%
“…Most of the JAG1 mutations detected in AGS patients mapped to the extracellular and trans-membrane domains of the protein and led to a premature termination codon, inhibiting the Notch signaling pathway in 70% of the individuals. [11,12] The underlying pathogenic mechanism of AGS remains unclear. Haploinsufficiency for the JAG1 gene has been proposed as the primary mechanism responsible for AGS since patients with large deletions including the entire JAG1 gene have phenotypes similar to those with intragenic mutations.…”
Section: World Journal Of Pediatricsmentioning
confidence: 99%
“…Sporadic mutations are commonly observed [2,3]. Recent molecular studies revealed that the JAG1 gene is mutated in 94% of patients with Alagille syndrome [4]. JAG1 encodes the protein Jagged1, a Notch ligand [5], whose signaling plays a role in organogenesis and is required for renal development in mice [6].…”
Section: Introductionmentioning
confidence: 99%